Behavioral Changes of Independent Palm Smallholders Farmers through Farmer Institution - Nurliza Nurliza; Fauyan (Jurnal Penyuluhan, 2021)
Farmer institutions along with regulatory, normative, and cultural cognitive aspects have important roles in social cohesion to achieve the food security of independent palm smallholder farmer households. However, some dysfunctionalities and external challenges affect the structure of their institutions. This paper aims to find ways to change the behavior of independent palm smallholder farmers by identifying the internal and external factors of their behaviors in their institutions. The data were collected from 100 smallholders in West Kalimantan using Structural Equation Model (SEM). The results indicate that the internal factors do not influence farmers’ behavior because of lack of social influences on their relationships, exceptional characteristics of the region, and a mismatch between perceived risk sources and risk management strategies. Meanwhile, the external factors (the surrounding environment, institutional information, the extension roles, ISPO, reward, and family encouragement) show positive influences on farmers' behavior. Therefore, to optimize the behavioral changes of independent palm smallholders in their institutions, knowledge exchange is necessary through formal or informal communication networks. Also, they need to have the connections with institutional buyers and potential agro-processing entrepreneurs and the connection with appropriate formal saving schemes, and financial products in their value chains.